The Foundation of the Modern National Economy and Discipline over Its Monetary Discourse: A Consideration from the Perspective of Polanyian Economics - Wakabayashi, Shigetaro (Journal of Economic Issues (Taylor & Francis Ltd), 2010)
How does the causality between society and the economy run? After examining this fundamental question from the perspective of Polanyian economics, we conclude that the modern national economy is where bargained exchange is institutionalized by society to pre-exist with the aid of discipline over currency issues. However, this discipline is not provided with a proper institutional defense; and potential fragility of the modern national economy owing to this fact was most vividly revealed by central bankers' conduct in the great liquidity crisis of 2007/8. What are we to do for this?
Keywords: Polanyi's institutionalism; bankers' associations; banking industry - economic aspects; capitalists & financiers; commercial banking system; crises - economic aspects; currency discipline; discourse; discourse and discipline; liquidity (economics); monetary policy; money; negotiation - social aspects; society and the economy

Power and Progress: The Swing of the Pendulum - Stewart, Frances (Journal of Human Development & Capabilities, 2010)
This paper uses Polanyi's 1944 analysis of policy change—in which there are long-term swings from state regulation to markets and back again, as the consequences of one regime lead to political reactions that in turn reverse the policies. It shows how the Polanyi analysis continued to apply throughout the twentieth and early-twenty-first century, well beyond when he wrote, and that the swings also apply to developing country policy-making. It argues that there are new signs of policy change—this time against market domination—in a number of developing countries. The paper concludes that Polanyi's view of the conditions behind policy change—notably long-term political movements, political struggle and political conflict—needs to be introduced into the analysis of policy change for the promotion of human development and the expansion of capabilities.
Keywords: developing countries; government policy; human development; legislation; policy sciences; policy swings; political economy; political planning

Globalisation and the Commodification of Labour: Temporary Labour Migration - Rosewarne, Stuart (Economic and Labour Relations Review, 2010)
There has been a qualitative shift in the character of international labour migration with increased temporary labour migration. With circumscribed employment rights, the increased significance of temporary migrant workers underscores arguments that globalisation has engendered a more profound commodification of labour. The instrumentalist approach, especially of international financial institutions in promoting temporary labour migration as a panacea for development, reinforces this impression. Encapsulated in migration-development discourse, labour migration, like other commodities, is presented as a means of generating export revenue for the South. Karl Polanyi's critique of this market-defined construct of labour as a commodity, when labour can only ever be a fictitious commodity, provides a basis for contesting the representation of labour in the migration-development discourse. However, recourse to a Marxist method is held to be essential if we are to move beyond an appreciation of the process in order to interrogate the rationale that is driving the transformation of labour.
Keywords: Marxian; Sraffian; commodification; current heterodox approaches: socialist; fictitious commodities; geographic labor mobility; globalization; immigrant workers; labor migration; labour migration; migrant; migrant workers; migration; value theory

From Menger to Polanyi: The Institutional Way - Cangiani, Michele (Austrian Economics in Transition, 2010)
The crisis of the institutions of liberal capitalism dates back to the last decades of the nineteenth century. Economics was thenceforth forced to radically reconsider its achievements and even its basic presuppositions, to the extent that they were linked to a free-market and perfect-competition model.
Keywords: economic history; economic systems; economic theory; financial economics; history of economic thought; international economics; macroeconomics; mathematical methods; methodology; monetary economics; quantitative economics

Are markets everywhere? : Ludwig von Mises, Friedrich Hayek and Karl Polanyi - Rodigues, Joao (The University of Manchester, 2010)
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; MISES, Ludwig von

Karl Polanyi, Athens and us: the contemporary significance of Polanyi's thought - Wjuniski, Bernardo Stuhlberger; Fernandez, Ramón G. (Revista de Economia Política, 2010)
Karl Polanyi is considered one of the most prominent social scientists of the 20th century. In his writings, an important concern was the relationship between the markets and the society (therefore, the state) as a whole; to discuss it, he introduced the concept of "embeddedness", fundamental for his study of the origins and consequences of the Industrial Revolution. An important part of his heritage is the study of the economic history of what he called "ancient societies," especially of Classical Greece. Polanyi used these studies to compare the ancient societies with his own times, in an effort to understand them all. This paper aims to relate Polanyi's work on the Athenian society with his studies about the modern times, showing that it is possible to draw lessons from Polanyi's thought on the relationship between the society, the state and the market that can help to design a political agenda for our days. In the first part, we present the most important aspects o the life and work of Polanyi, and in the second we discuss the most important aspects of his worldview. Then, in the third part, we study his view of the early Athenian economy; mainly, we focus on the coexistence of a kind of state planning and a market, showing how this understanding is crucial for the whole Polanyian legacy, with its emphasis in the comparison of different societies and times. We conclude by underlining the relevance of this interpretation advanced by Polanyi to understand the societies of our days, focusing on some proposals to extend his approach to deal with our contemporary problems.
Keywords: classical Greek economy; economic history; embeddedness

The Rise and Fall of the Market Economy - Zaman, Asad (Review of Islamic Economics, 2010)
The core economic functions of production and distribution of goods can be handled by many different methods. After the fall of communism, the market mechanism has become nearly universal. Conventional economic theories argue that this is natural, because it is the best and the most efficient method for organizing economic affairs in a society. This paper, based on the analysis of Polanyi (1944) and Klein (2008) argues that the opposite is true. Market mechanisms conflict with natural mechanisms for production and exchange in traditional societies. Unregulated markets cause tremendous damage, as can be witnessed today in terms of countless economic crises, wars, environmental destruction, as well as damage to social networks. Because of this damage, market societies can only be maintained by force, as well as disinformation. To resolve crises on myriad fronts caused by the unregulated market, it is the need of the hour to find viable alternatives.
Keywords: capitalist systems: performance and prospects; comparative analysis of economic systems; cultural economics: religion; other economic systems: performance and prospects

The Role of the State in Making a National Market: The Evolution of the Grain Market in China (1978-2000) - Zhou, Wubiao (China Agricultural Economic Review, 2010)
The paper aims to examine Karl Polanyi's view of market evolution in the context of the emergence of a national grain market in China's transition economy. The dataset used includes information about inter-provincial grain trade on China's grain market from November 1999 to October 2000. A priori blockmodelling method is used for hypothesis testing. This paper finds that a partially integrated national grain market had emerged at the beginning of the twenty-first century in China in spite of local protectionism. Additionally, the emergence of this market is found to be partly a result of the reform-oriented state's attempt to create national wholesale grain markets.
Keywords: agricultural policy; agriculture; agriculture: aggregate supply and demand analysis; collectives; communes; economic development: agriculture; energy; environment; food policy; natural resources; other primary products; prices